Captive white‐tailed deer industry—Current status and growing threat - Kip P. Adams; Brian P. Murphy; Matthew D. Ross (Wildlife Society Bulletin)
ABSTRACT In 2012, 10 states in the United States debated legislation to introduce or expand captive white‐tailed deer (Odocoileus virginianus) breeding operations. Because this was far more than any prior year, we surveyed 37 state wildlife agencies in the eastern contiguous United States to determine the scope and intensity of captive operations and state‐specific requirements. Thirty‐seven states provided some data. Twenty of 32 states reported 5–1,332 breeding facilities holding >140,000 white‐tailed deer; 20 of 29 states reported 1–150 shooting preserves holding >25,000 white‐tailed deer. Captive white‐tailed deer were classified as wildlife in 12 of 22 states (55%), livestock in 8 states (36%), and game animals in 2 states (9%). Only 5 of 21 states (24%) had minimum acreage requirements for breeding facilities, but 13 of 20 states (65%) did for shooting preserves. Four of 16 states (25%) had a minimum release time before deer could be shot in a preserve. Six of 21 states (29%) had stocking density requirements, with 6 of 25 states (24%) listing habitat requirements for captive white‐tailed deer facilities. Seventeen of 23 states (74%) required external tagging, and 24 of 27 states (89%) allowed consumption of white‐tailed deer killed in shooting preserves. We believe the captive white‐tailed deer industry undermines the North American Model of Wildlife Conservation, threatens the health of wild deer, and undermines the public's perception of hunting. A better understanding of this growing industry will help managers safeguard free‐ranging white‐tailed deer populations and the future of deer hunting. © 2016 The Wildlife Society.